THE UNFULFILLED LOVE AND BELONGING NEEDS FOUND BY THE MAIN CHARACTER IN “ANNA KARENINA” BY LEO TOLSTOY: PSYCHOLOGICAL APPROACH - Sianipar, Almita Rumiris; Jusmaya, Ance (LPPM Universitas Putera Batam, 2019)
The purpose of this research is to figure out what are causes and effects of unfulfilled love and belonging needs through intimacy in a couple in the main character in Anna Karenina by Leo Tolstoy (1877). In this research, researcher used the theory of Abraham H. Maslow (1970), the Hierarchy of Needs. This research is descriptive qualitative research, In the process of collecting data, researcher used the documentation method by reading the novel